Oaxaca in motion : an ethnography of internal, transnational, and return migration - Sandoval-Cervantes, Iván (University of Texas Press, 2022)
"The book looks at the different experiences of migrants from the Zapotec community of Zegache, in Oaxaca, Mexico, especially women who have migrated to Mexico City and men who have moved to Los Angeles and elsewhere in the United States. In particular, it focuses on gender and kinship and how different kinds of migration affect gender and kinship in different ways"--